Dataset of concentrations of legacy persistent organic pollutants in fishes and human of the European Arctic Russia - Andrey Aksenov (Zenodo, 2022)
The dataset presented in this Data descriptor supports “Persistent organic pollutants (POPs) in fish consumed by the indigenous peoples from Nenets Autonomous Okrug” (Lakhmanov et al., 2020).